Atmospheric Electricity Data From Lerwick During 1964 to 1984 - R. G. Harrison; H. Mkrtchyan; K. A. Nicoll (Geoscience Data Journal)
ABSTRACT A dataset of the atmospheric Potential Gradient (PG) from Lerwick observatory in Shetland is now available, which provides hourly‐averaged PG for each month, from January 1964 to July 1984. The measurements were made consistently, with calibrated and well‐maintained instrumentation. Co‐located meteorological observations are also available from the same site, where disturbing effects of air pollution are small. Other sources of atmospheric data such as satellite observations became increasingly abundant during the era of the measurements, making broader comparisons possible. On average, the Lerwick PG measurements contain a diurnal cycle characteristic of the global circuit and show relationships with the El Niño‐Southern Oscillation (ENSO), especially in December. The value of the data is in the information it contains about the global atmospheric electric circuit, which is embedded in the climate system.